Avaliação do processo de logística reversa pós-vendas no segmento farmacêutico - Giordano, Carlos Vital; Balbino Rainha, Gabriella; Gonçalves, Luiz Claudio; Bezerra Ribeiro, Patricia; da Silva Santos, Patricia Maria (Pontifícia Universidade Católica de São Paulo - PUC/SP, 2019)
This paper presents a study about the application of the Reverse Logistics practice in the business environment with a focus on the aftermarket process. In this sense, the objective was to evaluate the importance of Reverse aftermarket Logistics of medicines, particularly in their return and disposal process, also presenting the reasons for the return, as well as the procedures performed. To illustrate the applicability of the process, a case study was carried out in a pharmaceutical industry located in the city of São Paulo.

O presente artigo apresenta um estudo sobre a aplicação da prática de Logística Reversa no ambiente empresarial com foco no processo de Pós-Vendas. Nesse sentido, o objetivo foi avaliar a importância da Logística Reversa Pós-Vendas  de medicamentos, particularmente em seu processo de devolução e descarte, apresentando também quais são os motivos para a devolução, bem como os procedimentos realizados. Para ilustrar a aplicabilidade do processo foi realizado um estudo de caso em uma indústria farmacêutica instalada na cidade de São Paulo.
Evaluation of the Aftermarket Reversal Logistics Process in the Pharmaceutical Sector
Keywords: Reverse logistics aftermarket; Devolution; Pharmaceutical Industry